Outcome of the Pediatric Patients with Portal Cavernoma: The Retrospective Study for 10 Years Focusing on Recurrent Variceal Bleeding - Hongjie Guo; Fabao Hao; Chunbao Guo; Yang Yu (Gastroenterology Research and Practice)
Background. Portal cavernoma (PC) is the most critical condition with risk or variceal hemorrhage in pediatric patients. We retrospectively investigated the patients with PC focusing on the predictors for recurrent variceal bleeding. Methods. Between July 2003 and June 2013, we retrospectively enrolled all consecutive patients admitted to our department with a diagnosis of PC without abdominal malignancy or liver cirrhosis. The primary endpoint of this observational study was recurrent variceal bleeding. Independent predictors of recurrent variceal bleeding were identified using the logistic regression model. Results. A total of 157 patients were enrolled in the study. During the follow-up period, 24 patients exhibited onset of recurrent variceal bleeding. Acute variceal bleeding was subjected to conservative symptomatic treatment and emergency endoscopic sclerotherapy. Surgical procedure selection was based on the severity of vascular dilation and collateral circulation. Multivariate logistic regression analysis demonstrated that the presence of ascites, collateral circulation, and portal venous pressure were independent prognostic factors of recurrent variceal bleeding for patients with portal cavernoma. Conclusions. The presence of ascites, collateral circulation, and portal venous pressure evaluation are important and could predict the postsurgical recurrent variceal bleeding in patients with portal cavernoma.